VP165 Landscape Assessment: Patient Engagement In Health Technology Assessment. (2017) - Oehrlein, Elisabeth; Harris, Jason; Labkoff, Nicole; Perfetto, Eleanor; Ziadeh, Manal; El-Gendi, Sarah; Ghorashi, Bahareh; Boutin, Marc
Abstract : INTRODUCTION: Understanding the current landscape of patient engagement across value decision-making bodies internationally is a critical first step toward improving the patient centricity of Health Technology Assessment (HTA). This study assessed: (i) Terms and definitions used; (ii) Patient engagement opportunities; (iii) Evidence of patient engagement. METHODS: A sample of country-specific HTA's (HTA; n = 6), professional organizations (PO; n = 4), and collaborations/independent organizations (CO; n = 3) was selected for representativeness. Information was gathered through: (i) targeted web search and (ii) emailing organizations directly. Definitions, HTA methods documents, and the three most recent evaluations were identified, abstracted, and compared. Data were collected between September-October 2016. RESULTS: Numerous terms are used to describe patient engagement: patient input (HTA = 1, PO = 1), patient-group submitted information (HTA = 1), cooperation with patients/users (HTA = 1), public consultation (HTA = 1), patient perspectives (HTA = 1, PO = 1), involvement of people affected (HTA = 1), patient involvement (HTA = 2), patient and public involvement (HTA = 1), lay involvement (HTA = 1), inclusion of patient representative (PO = 3), patient reports (PO = 1), patient preference (PO = 2), public consultation (CO = 1), stakeholder consultation (CO = 1), open input (CO = 1), stakeholder engagement (CO = 1), and patient participation (CO = 1). Opportunities for patient engagement were described as: patient questionnaire (HTA = 2); comment period (HTA = 1; CO = 1); committee participation (HTA = 3; PO = 3); propose topics (HTA = 1); draft guidance (HTA = 1); general stakeholder forum (CO = 1). While organizations outline opportunities for patient engagement, not all organizations have clear evidence the practices are used or have impact. Recent evaluations demonstrate clear evidence of engagement (HTA = 2); Unclear or mixed evidence (HTA = 1; PO = 1; CO = 2); No evidence (HTA = 3; PO = 3; CO = 1). CONCLUSIONS: There is substantial heterogeneity in the terms used to describe patient engagement activities across organizations. While a variety of opportunities for patient engagement are described, lack of clear evidence to how patient engagement practices are consistently used may contribute to the perception that engagement by HTAs.